Dibutyl phthalate exposure alters T‐cell subsets in blood from allergen‐sensitized volunteers. (19th April 2022) - Maestre‐Batlle, Danay; Nygaard, Unni C.; Huff, Ryan D.; Alexis, Neil E.; Tebbutt, Scott J.; Turvey, Stuart E.; Carlsten, Christopher; Kocbach Bølling, Anette
Abstract: Phthalates are ubiquitous environmental contaminants associated with allergic disease in epidemiological and animal studies. This investigation aims to support these associations by interrogating systemic immune effects in allergen‐sensitized volunteers after controlled indoor air exposure to a known concentration of dibutyl phthalate (DBP). The phthalate‐allergen immune response (PAIR) study enrolled 16 allergen‐sensitized participants to a double‐blinded, randomized, crossover exposure to two conditions (DBP or control air for 3 hr), each followed immediately by inhaled allergen challenge. Peripheral blood immune cell composition and activation along with inflammatory mediators were measured before and after exposure. DBP exposure prior to the inhaled allergen challenge increased the percentage of CD4 + T helper cells and decreased the percentage of regulatory T cells (3 hr and 20 hr post‐exposure), while only modest overall effects were observed for inflammatory mediators. The cells and mediators affected by the phthalate exposure were generally not overlapping with the endpoints affected by allergen inhalation alone. Thus, in distinction to our previously published effects on lung function, DBP appears to alter endpoints in peripheral blood that are not necessarily enhanced by allergen alone. Further studies are needed to clarify the role of phthalate‐induced systemic effects in disease pathogenesis.